2021
DOI: 10.1088/1748-9326/abfa4f
|View full text |Cite
|
Sign up to set email alerts
|

An intervention study of the rural elderly for improving exposure, risk perception and behavioral responses under high temperature

Abstract: The frequency and intensity of high-temperature events continue to increase, resulting in a surge of pathogenicity and mortality. People with low levels of risk perception and adaptability, such as the elderly, suffer more from high temperatures. Effective intervention measures may lead to reduced levels of high temperature-related risk. The purpose of this study was to compare changes in temperature exposure, risk perception and coping behaviors under different intervention methods. Herein we conducted three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Therefore, education should be one underlying and prioritised policy in response to climate change, which can be done by formulating environmental campaigns and practices, information circulating by mass media, and community buddy systems. The effectiveness of education has been backed up by Lou et al (2021), who indicated in an intervention study that education is more effective in leading to higher levels of risk perception and more behavioural responses among the rural elderly in Jiangsu Province, China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, education should be one underlying and prioritised policy in response to climate change, which can be done by formulating environmental campaigns and practices, information circulating by mass media, and community buddy systems. The effectiveness of education has been backed up by Lou et al (2021), who indicated in an intervention study that education is more effective in leading to higher levels of risk perception and more behavioural responses among the rural elderly in Jiangsu Province, China.…”
Section: Discussionmentioning
confidence: 99%
“…Additional subsidy support from local governments, departments, and agencies is also essential to ensure the implementing of adaptive response practices. For example, Lou et al (2021) suggested that subsidy support can promote home cooling practices among the elderly exposed to high temperatures. Following the advancement of technologies, smart sensors deployed in the workplace or houses may help to monitor the health status of individuals in order to provide timely notification (Lee et al, 2017; Robben et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Malawi reached similar conclusions that when the exposure level decreased, the perceived risk level of the case group residents increased [ 33 ]. In addition, an experiment on a heat exposure intervention found that protective behavior scores were higher in the case groups than in the controls [ 27 ]. In our study specifically, not only familiarity with the project, benefit from the project, support for project, and trust in government, but also willingness to open windows and to pay for clean coal, were higher in the case group than in the control group; however, a significant difference in effect was not found, with the possible explanation that the original stove and coal had a strong effect on both the case and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the sources and the concentrations of air pollutants helps to establish the new regulations for control measures. This subsequently leads to the diminishing mortality of infants and children under the age of five [25], the elderly [196,197], and the low-income population [194,195]. Short-term public health activities to decrease heat-related morbidity should target sensitive population groups to assure access to air conditioning, evaporative coolers, fans, adequate fluid intake, etc.…”
Section: Prevention Policymentioning
confidence: 99%
“…Short-term public health activities to decrease heat-related morbidity should target sensitive population groups to assure access to air conditioning, evaporative coolers, fans, adequate fluid intake, etc. [194,195,197]. On the other hand, on hot days, emissions of pollutants may be further increased by behavioral changes when inhabitants of cities may choose to use their possibly air-conditioned car more often [79].…”
Section: Prevention Policymentioning
confidence: 99%